Potential Applications of Image-Guided Radiotherapy for Radiation Dose Escalation in Patients with Early Stage High-Risk Prostate Cancer - Nguyen, Nam P.; Davis, Rick; Bose, Satya R.; Dutta, Suresh; Vinh-Hung, Vincent; Chi, Alexander; Godinez, Juan; Desai, Anand; Woods, William; Altdorfer, Gabor; D’Andrea, Mark; Karlsson, Ulf; et al. (Frontiers in Oncology, 2015)
Patients with early stage high-risk prostate cancer (PSA >20, Gleason score >7) are at high risk of recurrence following prostate cancer irradiation. Radiation dose escalation to the prostate may improve biochemical free survival for these patients. However, high rectal and bladder dose with conventional three-dimensional conformal radiotherapy (3D-CRT) may lead to excessive gastrointestinal and genitourinary toxicity. Image-guided radiotherapy (IGRT), by virtue of combining the steep dose gradient of intensity-modulated radiotherapy (IMRT) and daily pretreatment imaging, may allow for radiation dose escalation and decreased treatment morbidity. Reduced treatment time is feasible with hypofractionated IGRT and it may improve patient quality of life.